Analysis of patients, reasons attendance to emergency service carried out by the Department of Ophthalmology Medical University of Warsaw - Langwińska-Wośko, Ewa; Wójcicka, Izabella; Gajda, Sebastian (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The aim of this study was to assess the percentage of purposeful attendance to ophthalmology emergency service and to analyse the main reasons of attendance. The authors analysed a group of over 40 thousand patients, and came to the conclusion that at least, one third of them should not have sought help in emergency service since their status did not justify that.